Profile of The Assessment of Pediatric Puyer Prescriptions at The Malili Public Health Center - Nurlina, Nurlina; Aztriana, Aztriana; Awalia, Andi Almayra Putri (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aimed to analyze the assessment profile of pediatric compounded powder prescriptions at the Malili Community Health Center for the period October–December 2023, focusing on the completeness of administrative, pharmaceutical, and clinical aspects based on the Indonesian Minister of Health Regulation No. 74/2016. The research also aimed to identify potential incompatibilities, ensure accurate dosage, and assess potential drug interactions. Research Method: A quantitative, descriptive, cross-sectional design with retrospective data collection was employed. A total of 237 pediatric compounded powder prescriptions, selected using Slovin’s formula from 1,215 prescriptions, met the inclusion criteria. Data were analyzed descriptively to evaluate compliance percentages across administrative, pharmaceutical, and clinical parameters. Results and Discussion: Administrative completeness reached 100% for patient name, age, doctor’s name, initials, date, and unit of origin; however, patient weight was 83.96%, while height and gender were absent, and the doctor’s SIP number was 38.39%. In pharmaceutical aspects, drug name, form, dosage, quantity, and usage instructions met 100% compliance, while strength of preparation was 26.16%. No drug incompatibilities were found. Clinically, treatment duplication and timeliness reached 100%, but dosage errors (underdose, overdose) and drug interactions (74.26%) were identified. Implications: The findings underscore the need to enhance prescription completeness, particularly in terms of drug strength, SIP number, and patient anthropometric data, to align with national pharmaceutical service standards and improve patient safety. Further training for prescribers and pharmacists is recommended.